Evaluation of the Antitumor Effects of BPR1J-340, a Potent and Selective FLT3 Inhibitor, Alone or in Combination with an HDAC Inhibitor, Vorinostat, in AML Cancer - Lin, Wen-Hsing; Yeh, Teng-Kuang; Jiaang, Weir-Torn; Yen, Kuei-Jung; Chen, Chun-Hwa; Huang, Chin-Ting; Yen, Shih-Chieh; Hsieh, Shu-Yi; Chou, Ling-Hui; Chen, Ching-Ping; Chiu, Chun-Hsien; Kao, Li-Chun; et al. (PLOS ONE, 2014)
Overexpression or/and activating mutation of FLT3 kinase play a major driving role in the pathogenesis of acute myeloid leukemia (AML). Hence, pharmacologic inhibitors of FLT3 are of therapeutic potential for AML treatment. In this study, BPR1J-340 was identified as a novel potent FLT3 inhibitor by biochemical kinase activity (IC50 approximately 25 nM) and cellular proliferation (GC50 approximately 5 nM) assays. BPR1J-340 inhibited the phosphorylation of FLT3 and STAT5 and triggered apoptosis in FLT3-ITD+ AML cells. The pharmacokinetic parameters of BPR1J-340 in rats were determined. BPR1J-340 also demonstrated pronounced tumor growth inhibition and regression in FLT3-ITD+ AML murine xenograft models. The combination treatment of the HDAC inhibitor vorinostat (SAHA) with BPR1J-340 synergistically induced apoptosis via Mcl-1 down-regulation in MOLM-13 AML cells, indicating that the combination of selective FLT3 kinase inhibitors and HDAC inhibitors could exhibit clinical benefit in AML therapy. Our results suggest that BPR1J-340 may be further developed in the preclinical and clinical studies as therapeutics in AML treatments.